Pengembangan Life Skill Entrepreneurship Siswa di SMAN 1 Maumere Melalui Ekstrakurikuler Kewirausahaan - Susilowati, Hari; Handayani, Trisakti (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This research aims to analyze the implementation of entrepreneurial extracurricular activities in developing the life skills of entrepreneurship students at SMAN 1 Maumere. This type of research is descriptive qualitative. The place of research was at SMAN 1 Maumere. Research sources were obtained from primary and secondary data. Primary data in the form of recordings from interviews with the Principal, Student Affairs Waka, extracurricular coordinator, teacher extracurricular entrepreneurship coaches, as well as some students involved in these activities. Secondary data in the form of notes, school documents, school profiles, pictures or photographs of activities, and archives relating to the problem under study. Collection techniques used methods of observation, interviews, and documentation. Test the validity of the data using source triangulation techniques. The results of the study are as follows: 1) the implementation of entrepreneurial extracurricular aims to develop students' interests and talents, 2) find out the factors that become obstacles in the implementation of activities, 3) Solutions to overcome these problems by intensifying all elements involved in the activities, as well as motivating students with various the event of the competition and exhibition of the results of entrepreneurial crafts.Keywords: Extracurricular Entrepreneurship, Entrepreneurship, Life SkillsÂ Abstrak: Tujuan dari penelitian ini untukmenganalisis pelaksanaan ekstrakurikuler kewirausahaan dalam pengembangan life skill entrepreneurship siswa di SMAN 1 Maumere. Jenis penelitian ini adalah bersifat deskriptif kualitataif. Tempat penelitian dilakukan di SMAN 1 Maumere. Sumber penelitian diperoleh dari data primer dan sekunder. Data primer berupa hasil rekaman dari wawancara kepada Kepala Sekolah, Waka bidang Kesiswaan, koordinator ekstrakurikuler, guru pembina ekstrakurikuler kewirausahaan, serta beberapa siswa yang terlibat dalam kegiatan tersebut. Data Sekunder berupa catatan, dokumen sekolah, profil sekolah, gambar atau foto-foto kegiatan, serta arsip yang berkaitan dengan masalah yang diteliti. Teknik pengumpulan menggunakan metode observasi, wawancara dan dokumentasi. Uji keabsahan data menggunakan teknik trianggulasi sumber. Hasil penelitian sebagai berikut: 1) pelaksanaan ekstrakurikuler kewirausahaan bertujuan untuk mengembangkan minat dan bakat siswa, 2) mengetahui faktor yang menjadi hambatan dalam pelaksanaan kegiatan, 3) Solusi mengatasi masalah tersebut dengan mengintesifkan semua unsur yang terlibat dalam kegiatan, serta memberikan motivasi siswa dengan berbagai ajang perlombaan dan pameran hasil kerajinan kewirausahaan.Kata kunci: Ekstrakurikuler Kewirausahaan, Life SkillEntrepreneurship